La rebelión de Galbaud y la libertad general de los esclavos de Saint-Domingue (1793-1794) - Atsè Alexis-Camille Kimou (Nuevo mundo - Mundos Nuevos, 2014)
The slaves rebellion of Saint-Domingue, led to the General freedom of the blacks after their contribution to the victory of the civil commissioners on Galbaud. Indeed, faced with the threat of Galbaud, sonthonax and Polverel decided to agree to release all Blacks that would accept fight for the Republic against the military forces of general Galbaud, appointed governor by the metropolis. The Blacks who were accepted this offer received freedom in exchange for services provided to French authorities in the defeat of the rebel Galbaud.